LUBANG RESAPAN BIOPORI SEBUAH STRATEGI UNTUK MEMANFAATKAN AIR HUJAN DALAM MENJAGA KELESTARIAN SUMBER AIR DI KOTA BANDAR LAMPUNG - Purwadi, Ofik Taufik; Yulianto, Herza; Mashabi, Mashabi (UNIVERSITAS LAMPUNG, 2014)
The basic principles of water conservation is to prevent the water lost as surface streams and save them as fully as possible into the body of the Earth. A form of utilization of rain water can be done by way of accommodating direct rainwater that falls on the surface of the Earth or water infiltrate into the ground. The first way is the direct way to reuse the rainwater that falls onto the surface of the ground by creating a pond or tub of rainwater collectors. Ways of utilization of rain water with water infiltrate into the soil can be done by make: infiltration well; and/or the infiltration hole biopori. Infiltration Hole Biopori is one technology that has been developed by Brata, these technologies effectively to reduce the potential for flooding and increase soil water reserves through utilization of rain water. Method of making Hole Resapan Biopori it has been widely de- veloped in some area (Jakarta, Jogjakarta etc.), because the technology is so cheap, easy and effi - cient. In the city of Bandar Lampung, the utilization of rain water has not done much, only a few establishments that have been doing this activity. The Agency has articulated the rainwater uti- lization progam was TAPS and AGENCY. At the community level city Bandar Lampung, the use of biopori still sound familiar so that the required infiltration hole making biopori socialization. Making the biopori infiltration hole, it can provide convenience for people living in crowded envi - ronments with land/environment is limited given the size of the biopori infiltration small hole with a diameter of 10 cm and a depth of 100 cm. Making the biopori infiltration hole it can provide in- put infiltration rain water into the ground to become groundwater. In order to perform groundwa - ter conservation through utilization of rain water by making biopori infiltration hole.